OP0222 Secukinumab provides sustained improvements in the signs and symptoms of active psoriatic arthritis: 104 weeks results from a phase 3 trial, future 2. (15th June 2017) - McInnes, IB; Mease, PJ; Ritchlin, C; Rahman, P; Gottlieb, A; Kirkham, B; Kajekar, R; Delicha, EM; Pricop, L; Mpofu, S; ,
Abstract : Background: Secukinumab significantly improved the signs and symptoms of psoriatic arthritis (PsA) over 52 weeks (wks) in FUTURE 2 study (NCT01752634 ). 1, 2 Objectives: To present longer-term (104 wks) efficacy and safety data of secukinumab from FUTURE 2 study. Methods: Overall, 397 patients (pts) with active PsA were randomised to secukinumab (300, 150, or 75 mg) or placebo at baseline, Wks 1, 2, 3, and 4, and every 4 wks thereafter. Assessments at Wk 104 are from pts originally randomised to secukinumab and included ACR20/50/70, PASI 75/90, DAS28-CRP, SF-36 PCS, HAQ-DI, dactylitis, and enthesitis. Multiple imputation was used for analysis of binary variables and mixed-model repeated measures for continuous variables. Analyses stratified by anti-TNFα status (naïve/inadequate response or intolerance to these agents) were prespecified and are reported as observed. Safety analysis included all pts who received ≥1 dose of secukinumab. Results: In total, 86/100 (86.0%), 76/100 (76.0%) and 65/99 (65.7%) pts in the secukinumab 300, 150, and 75 mg groups respectively completed 104 wks. Sustained clinical improvements were observed through Wk 104 with secukinumab across all clinically important domains of PsA (Table). Responses were sustained through Wk 104 regardless of anti-TNFα status. Over the entire treatment period (mean [±SD] exposure to secukinumab of 709±210.99 days), the exposure adjusted incidence rates for serious infections/infestations, candida infections, inflammatory bowel disease and malignant/unspecified tumors with secukinumab were 1.6, 2.3, 0.5 and 1.3, respectively. Conclusions: Secukinumab 300 and 150 mg provided sustained improvements in signs and symptoms and multiple clinical domains of active PsA through 2 years of therapy. Secukinumab was well tolerated, with a safety profile consistent with that reported previously. References: McInnes IB, et al. Lancet 2015;386:1137–46. McInnes IB, et al. Ann Rheum Dis. 2015;74:352–3. Disclosure of Interest: I. McInnes Grant/research support from: Abbvie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, and UCB, Consultant for: Abbvie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, and UCB, Speakers bureau: Abbvie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, and UCB, P. Mease Grant/research support from: Abbvie, Amgen, BMS, Celgene, Crescendo Bioscience, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, Consultant for: Abbvie, Amgen, BMS, Celgene, Crescendo Bioscience, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, Speakers bureau: Abbvie, Amgen, BMS, Celgene, Crescendo Bioscience, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, C. Ritchlin Grant/research support from: Amgen, UCB, Abbvie, Novartis, and Janssen, Consultant for: Amgen, UCB, Abbvie, Novartis, and Janssen, Speakers bureau: Amgen, UCB, Abbvie, Novartis, and Janssen, P. Rahman Consultant for: Abbott, Abbvie, Amgen, BMS, Celgene, Janssen, Novartis, Pfizer and Roche. Consultant for pharmaceutical companies dealing with biologic agents in rheumatology, A. Gottlieb Grant/research support from: (paid to Tufts Medical Center until 5/11/16 thereafter: None): Centocor (Janssen) Inc., Amgen, Abbott (AbbVie), Novartis, Celgene, Pfizer, Lilly, Levia, Merck, Xenoport, Dermira, Baxalta, Consultant for: Amgen Inc., Astellas, Akros, Centocor (Janssen) Inc., Celgene Corp., Bristol Myers Squibb Co., Beiersdorf Inc., Abbott Labs. (AbbVie), TEVA, Actelion, UCB, Novo Nordisk, Novartis, Dermipsor Ltd., Incyte, Pfizer, Canfite, Lilly, Coronado, Vertex, Karyopharm, CSL Behring Biotherapies for Life, Glaxo SmithKline, Xenoport, Catabasis, Meiji Seika Pharma Co. Ltd, Takeda, Mitsubishi, Tanabe Pharma Development America Inc., Genentech, Baxalta, Kineta One, KPI Therapeutics, Crescendo Bioscience, Aclaris, Amicus and Reddy Labs, B. Kirkham Grant/research support from: Abbvie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Roche, and UCB, Consultant for: Abbvie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Roche, and UCB, Speakers bureau: Abbvie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Roche, and UCB, R. Kajekar Shareholder of: Novartis, Employee of: Novartis, E. M. Delicha Employee of: Novartis, L. Pricop Shareholder of: Novartis, Employee of: Novartis, S. Mpofu Shareholder of: Novartis, Employee of: Novartis